2018
DOI: 10.1080/2162402x.2018.1500673
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 receptor signaling is essential for control of hepatocellular carcinoma growth and immunological memory for tumor challenge

Abstract: Hepatocellular carcinoma (HCC) is a typical inflammation-associated cancer. IL-21 regulates both innate and adaptive immune responses and has key roles in antitumor and antiviral responses. However, the role of IL-21 in HCC development is poorly defined. In the current study, we explored the role of IL-21R signaling in HCC growth by using IL-21R knockout mice and HCC mouse models. We discovered that IL-21R signaling deficiency promoted HCC growth in tumor-bearing mice. We showed that IL-21R deletion reduced T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
(53 reference statements)
0
15
0
Order By: Relevance
“…First, high expression of IL-21R on CD8 + T cells in tumors correlates positively with overall survival and lack of tumor recurrence in hepatocellular carcinoma (HCC) patients 24 . Second, in mice, IL-21R signaling reduces accumulation of myeloid derived suppressor cells (MDSCs) in the TME to control rapid HCC growth and maintains an immunological memory response to tumor re-challenge 24 . Third, newly diagnosed HER2 + breast cancer patients with higher Il21r expression may have a reduced risk of distant relapse when treated with trastuzumab (anti-HER2/ErB2 mAb) in combination with chemotherapy; IL-21R expression on CD8 + effector T cells, not NK cells, is required for optimal anti-ErB2 mAb efficacy 25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, high expression of IL-21R on CD8 + T cells in tumors correlates positively with overall survival and lack of tumor recurrence in hepatocellular carcinoma (HCC) patients 24 . Second, in mice, IL-21R signaling reduces accumulation of myeloid derived suppressor cells (MDSCs) in the TME to control rapid HCC growth and maintains an immunological memory response to tumor re-challenge 24 . Third, newly diagnosed HER2 + breast cancer patients with higher Il21r expression may have a reduced risk of distant relapse when treated with trastuzumab (anti-HER2/ErB2 mAb) in combination with chemotherapy; IL-21R expression on CD8 + effector T cells, not NK cells, is required for optimal anti-ErB2 mAb efficacy 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several lines of evidence indicate that IL-21R is involved in tumor immunity. First, high expression of IL-21R on CD8 + T cells in tumors correlates positively with overall survival and lack of tumor recurrence in hepatocellular carcinoma (HCC) patients 24 . Second, in mice, IL-21R signaling reduces accumulation of myeloid derived suppressor cells (MDSCs) in the TME to control rapid HCC growth and maintains an immunological memory response to tumor re-challenge 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no clinical association between IL21R deficiency and liver malignancy has been described in humans, an interesting mice model demonstrated that IL21R signaling deficiency might promote hepatocellular carcinoma (HCC) growth. Interestingly, Zheng et al reported that IL21R deletion reduced T cells infiltration, activation and functions while increased the infiltration of myeloid-derived suppressor cells that enhanced HCC growth (127). If confirmed in human studies, this finding could affect long-term follow-up strategies of liver involvement in IL21R-deficient patients.…”
Section: Il21rmentioning
confidence: 96%
“…In acute viral infections, IL-21R signaling is essential for the proliferation and survival of activated CD8 + T cells as well as the generation of long-lived memory cells (25)(26)(27). However, the function of IL-21R signaling in cancer is controversial and not completely understood (28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%